Conservative Management of a Delayed Neovesicocutaneous Fistula - Koichi Kodama; Yasukazu Takase; Isamu Motoi (Case Reports in Urology)
A neovesicocutaneous fistula is a rare complication after orthotopic bladder reconstruction, particularly in the late postoperative period. We report the case of a 59-year-old man who had undergone ileal neobladder construction 17 months previously. He presented with urinary retention concomitant with urinary tract infection due to a neovesicourethral anastomotic stricture. After a combination of transurethral catheter drainage and broad-spectrum antibiotic therapy for 3 weeks, the fistulous tract completely closed. Therefore, conservative treatment may be regarded as a valid option for a delayed neovesicocutaneous fistula.